2019
DOI: 10.1002/da.22908
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, depressive symptoms, and mortality risk in old age: The role of inflammation

Abstract: Background Both diabetes and depression increase the mortality risk in the elderly. In this study, we evaluated mortality risk associated with the comorbidity between depression and diabetes. We also assessed the moderating role of inflammation in the mortality risk in this population. Methods We included a total of 1,183 community‐dwelling older adults, divided into four groups: “neither diabetes nor depression”; “diabetes only”; “depression only,” and “both diabetes and depression,” and followed‐up for a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
2
9
0
1
Order By: Relevance
“…Additionally, depressive symptoms were significantly associated with sarcopenia in the subgroup with a higher level of DII score in the stratified analyses. Previous studies suggested the moderating effect of inflammation on the association between depression and adverse health outcomes (40), such as all-cause mortality (41), to some certain degree supporting our findings. Due to the relatively small number of participants with sarcopenia affecting the statistical power, stratified analyses did not demonstrate significant association in individuals with the highest tertile of DII.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, depressive symptoms were significantly associated with sarcopenia in the subgroup with a higher level of DII score in the stratified analyses. Previous studies suggested the moderating effect of inflammation on the association between depression and adverse health outcomes (40), such as all-cause mortality (41), to some certain degree supporting our findings. Due to the relatively small number of participants with sarcopenia affecting the statistical power, stratified analyses did not demonstrate significant association in individuals with the highest tertile of DII.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, these findings are in line with previous studies from Hispanic and non-Hispanic populations where both depression and diabetes are associated with increased inflammatory and metabolic markers (Diniz et al, 2010(Diniz et al, , 2016Smagula et al, 2016). They also expand recent findings suggesting that insulin resistance is associated with higher depressive symptoms in a predominantly first generation of Mexican American older adults, that higher inflammatory status can significantly increase mortality risk in older adults with depression and diabetes, and that abnormalities in the insulin signaling cascade are related to cognitive impairment in older adults with late-life depression (Castro-Costa et al, 2019;Diniz et al, 2011Diniz et al, , 2018.…”
supporting
confidence: 78%
“…Mental health comorbidities including depression are also increasing worldwide and worsen outcomes for population with diabetes. 8,9 As one of the important indexes to evaluate blood glucose levels, the association of glycosylated hemoglobin (GHb) levels with depression is still unclear. GHb is a product of the combination of carbohydrates in serum and hemoglobin in red blood cells.…”
Section: Introductionmentioning
confidence: 99%